2006
DOI: 10.1088/0967-3334/27/5/s04
|View full text |Cite
|
Sign up to set email alerts
|

Imaging cardiac activity by the D-bar method for electrical impedance tomography

Abstract: A practical D-bar algorithm for reconstructing conductivity changes from EIT data taken on electrodes in a 2D geometry is described. The algorithm is based on the global uniqueness proof of Nachman (1996 Ann. Math. 143 71-96) for the 2D inverse conductivity problem. Results are shown for reconstructions from data collected on electrodes placed around the circumference of a human chest to reconstruct a 2D cross-section of the torso. The images show changes in conductivity during a cardiac cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
136
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(139 citation statements)
references
References 26 publications
2
136
0
1
Order By: Relevance
“…We develop a re-formulation of the (Fourier transformed) ∂ equation based on the support properties of the solution for large k, which yields a once iterated variant of (8) and handles disparate support issues via careful shifting within the computational domain. Remarkably, this new equation is equivalent (up to a Fourier transform) of the iterated system of equations which Perry studies in ( [26]), and in fact can be effectively used for all values of k.…”
Section: (6)mentioning
confidence: 99%
See 1 more Smart Citation
“…We develop a re-formulation of the (Fourier transformed) ∂ equation based on the support properties of the solution for large k, which yields a once iterated variant of (8) and handles disparate support issues via careful shifting within the computational domain. Remarkably, this new equation is equivalent (up to a Fourier transform) of the iterated system of equations which Perry studies in ( [26]), and in fact can be effectively used for all values of k.…”
Section: (6)mentioning
confidence: 99%
“…In section 3 we present a short review on the existence theory for equation (8). In section 4 we discuss the numerical implementation of a regularization approach for |ξ| → 0 of the integrand in (8).…”
Section: (6)mentioning
confidence: 99%
“…Isaacson et al demonstrated in [IMNS04,IMNS06] that the D-bar method performs well on practical data measured from laboratory phantoms and from human subjects. The mandatory regularization step was provided by low-pass filtering in the nonlinear frequency domain.…”
Section: (B)mentioning
confidence: 99%
“…2009(a): The numerical evidence from practical imaging experiments [IMNS04,IMNS06] inspired a rigorous regularization proof of convergence in the form of (1.4), see [KLMS09]. This gave an answer to (iii) and outlined a method for choosing the regularization parameter as the inverse of the nonlinear cutoff frequency.…”
Section: (B)mentioning
confidence: 99%
“…See Figure 2.2 for an example of an image of the heart and lungs obtained from an actual impedance imaging system. The articles [5] and [11] provide a good general overview of the subject.…”
Section: Impedance Tomographymentioning
confidence: 99%